2012
DOI: 10.1111/j.1742-7843.2012.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between HLA and Stevens–Johnson Syndrome Induced by Carbamazepine in Southern Han Chinese: Genetic Markers besides B*1502?

Abstract: Previous studies have demonstrated a strong association between carbamazepine-induced Stevens-Johnson syndrome and toxic epidermal necrolysis (CBZ-induced SJS/TEN) and HLA-B*1502 in Chinese, and HLA-A*3101 but not HLA-B*1502 in Caucasians and Japanese. Cases with CBZ-induced SJS/TEN negative for HLA-B*1502 were reported recently in Southeast Asia. Negative correlations between CBZ-induced SJS/TEN and B*0702 or B*4001 have also been reported, suggesting a possible protective role. Here, we genotyped HLA-B and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 25 publications
2
64
0
1
Order By: Relevance
“…HLA-B*5701, HLA-B*5801, HLA-B*1502, HLA-A*3101, HLA-A*0206, HLA-B*4403, HLA-A29, HLA-B12, HLA-DR7, and HLA-A2 are linked to SJS drug hypersensitivity reactions. [38][39][40][41] HLA-DQB1*0601, HLA-DQA1*0103, DQB1*0301, and HLA-A*0206 are linked to ocular manifestations in SJS. 42 Genetic influences can explain why SJS occurs in multiple family members even though it is a rare condition 43 or why it recurs in certain individuals.…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…HLA-B*5701, HLA-B*5801, HLA-B*1502, HLA-A*3101, HLA-A*0206, HLA-B*4403, HLA-A29, HLA-B12, HLA-DR7, and HLA-A2 are linked to SJS drug hypersensitivity reactions. [38][39][40][41] HLA-DQB1*0601, HLA-DQA1*0103, DQB1*0301, and HLA-A*0206 are linked to ocular manifestations in SJS. 42 Genetic influences can explain why SJS occurs in multiple family members even though it is a rare condition 43 or why it recurs in certain individuals.…”
Section: Genetic Predispositionmentioning
confidence: 99%
“…Recent studies have found a significant association between CBZ-induced SJS HLA-A*3101 but not HLA-B*1502. These cases were reported in different populations including Caucasian [133], Japanese [134] and, most recently, Chinese [135] children.…”
Section: Pediatric Detection Of Adrs and Drug Toxicitymentioning
confidence: 98%
“…Other alleles have shown significant relationships with SJS/TEN within these ethnicities, such as HLAB*07:02 [98] and HLA-A*31:01 [100, 119-121]. Several studies in Japanese, Korean and Han Chinese patients suggest that carriers of the HLA-B*15:11 alleles [101, 105, 122] have an increased risk of developing SCARs. The average allele frequencies for *15:11 in Japanese and Korean populations are higher than for *15:02 , with values of 0.4 - 0.8% for the Japanese, and 1.6% for Koreans [6].…”
Section: Important Variantsmentioning
confidence: 99%
“…The average allele frequencies for *15:11 in Japanese and Korean populations are higher than for *15:02 , with values of 0.4 - 0.8% for the Japanese, and 1.6% for Koreans [6]. Both *15:02 and *15:11 are part of the same HLA-B75 serotype [101, 122], and the two alleles share a 98.6% amino acid sequence homology [105]. Therefore, they may share similar structures that lead to the triggering of an immune reaction when carbamazepine is administered [105].…”
Section: Important Variantsmentioning
confidence: 99%
See 1 more Smart Citation